Sphingosine 1-phosphate: Lipid signaling in pathology and therapy - Cartier, Andreane; Hla, Timothy (Science (American Association for the Advancement of Science), 2019)
Sphingosine 1-phosphate (S1P), a metabolic product of cell membrane sphingolipids, is bound to extracellular chaperones, is enriched in circulatory fluids, and binds to G protein-coupled S1P receptors (S1PRs) to regulate embryonic development, postnatal organ function, and disease. S1PRs regulate essential processes such as adaptive immune cell trafficking, vascular development, and homeostasis. Moreover, S1PR signaling is a driver of multiple diseases. The past decade has witnessed an exponential growth in this field, in part because of multidisciplinary research focused on this lipid mediator and the application of S1PR-targeted drugs in clinical medicine. This has revealed fundamental principles of lysophospholipid mediator signaling that not only clarify the complex and wide ranging actions of S1P but also guide the development of therapeutics and translational directions in immunological, cardiovascular, neurological, inflammatory, and fibrotic diseases.